An Analysis of Contextual Meaning in Olivia Rodrigo's Songs - Wijaya, Rivo Presti Roma; Rosita, Nur (English Language and Literature, 2023)
Contextual meaning is meaning that refers to context, or a sentence that can support the clarity of a meaning. This research was conducted to find the types of contextual meaning and changes in meaning in Olivia Rodridgo's songs entitled "drivers license", "deja vu", "good 4 u", "happier" and "traitor". This research used contextual meaning theory by from Pateda (2010) and semantic change theory by Chaer (2013). The method of this research was descriptive qualitative. The results showed that there were five out of 10 types of contextual meaning in the five songs, which context of person, context of situation, context of whether or not a formal conversation, context of speaker’s mood or listener’s mood and context of object with a total of 27 result, which contain nine words and 18 phrases. Also, three out of five types of meaning changes were found in words and phrases containing contextual meaning, which are widening, totally changed, and dysphemism with a total data of 17 out of 27 data, which contain of nine words and eight phrases. This research found that words or phrases that cannot be interpreted just by looking at the definitions in the dictionary, but also must be understood the context of their use.